Genome-wide association study of medication-use and associated disease in the UK Biobank - Yeda Wu (Nature Portfolio, 2019)
An understanding of the genetic variants associated with medication use may shed light on the underlying biological pathways of disease, and aid in drug development. Here, Wu and colleagues conduct a GWAS for self-reported medication-use in the UK Biobank, finding more than 500 independent variants and many promising leads for future work.